2017
DOI: 10.1016/j.neuroimage.2016.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Decoding hand gestures from primary somatosensory cortex using high-density ECoG

Abstract: Electrocorticography (ECoG) based Brain-Computer Interfaces (BCIs) have been proposed as a way to restore and replace motor function or communication in severely paralyzed people. To date, most motor-based BCIs have either focused on the sensorimotor cortex as a whole or on the primary motor cortex (M1) as a source of signals for this purpose. Still, target areas for BCI are not confined to M1, and more brain regions may provide suitable BCI control signals. A logical candidate is the primary somatosensory cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
118
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(130 citation statements)
references
References 48 publications
10
118
0
2
Order By: Relevance
“…Such results have been confirmed in invasive [23] and non-invasive [24] studies. It has also been shown that passive hand mobilizations induce similar brain patterns as those observable in active manual tasks [25].…”
Section: Brain-machinesupporting
confidence: 61%
“…Such results have been confirmed in invasive [23] and non-invasive [24] studies. It has also been shown that passive hand mobilizations induce similar brain patterns as those observable in active manual tasks [25].…”
Section: Brain-machinesupporting
confidence: 61%
“…These proof of concept technologies have enabled neurophysiologists to discover novel neural dynamics from the surface of the brain, including recurrent spiral waves manifested from seizures in animal model (Viventi et al, 2011) and single unit activity in both animal model and studies in the clinic (Khodagholy et al, 2016(Khodagholy et al, , 2014. These developments could lead to advances in basic neuroscience research and medical applications such as clinical mapping and brain-machine interfaces (Blakely et al, 2008;Bleichner et al, 2016;Branco et al, 2016;Chang, 2015;Ganji et al, 2017;Hwang and Andersen, 2013;Jiang et al, 2017;Kaiju et al, 2017;Kellis et al, 2010;Leuthardt et al, 2009;Maharbiz et al, 2017;Muller et al, 2016b).…”
mentioning
confidence: 99%
“…A more significant factor determining the specificity of EFP/ECoG signals, therefore, might be given by the size and density of the recording electrodes. Only few studies have compared signal quality and decoding performance for the different types of subdural and intracortical arrays used in clinical and basic neuroscience studies (Kellis et al, 2016;Flint et al, 2017;Wang et al, 2017), yet it appears that many of the results indicating high signal specificity were obtained with high-density arrays and rather small electrodes (Kaiju et al, 2017;Branco et al, 2017;Hu et al, 2018;Ramsey et al, 2018). The findings of the present study that EFPs possess high spatial selectivity is clearly in line with this: With the small electrodes of our array we estimated mean ERF sizes of about 2.7 and 2.8 deg diameter (re-calculated from ERF areas assuming circular ERFs) in monkeys M1 and M3, respectively, and 4.0 deg in M2, which is around a factor of 1.6 to 2.3 of the receptive field size of intracortical LFPs, measured with the same mapping paradigm (Drebitz et al, 2019).…”
Section: Discussionmentioning
confidence: 99%